2020
DOI: 10.1021/acs.joc.0c01253
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Pyrrolo[2,1,5-cd]indolizine Rings via Visible-Light-Induced Intermolecular [3+2] Cycloaddition of Indolizines and Alkynes

Abstract: A range of indolizine smoothly underwent visible-light-induced intermolecular [3+2] annulations with internal alkynes to afford pyrrolo­[2,1,5-cd]­indolizine in good to excellent yields with high regioselectivity. Through this cascade reaction, a series of fluoroactive fused indolizines with a large π-system were conveniently synthesized. The usage of visible light as energy source with air as a stoichiometric oxidant under simple conditions makes this process attractive and practical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…In spite of these great advances in selenofunctionalization, visible light-induced three-component cascade cyclization with chalcogens has never yet been documented. Because of our continuing interest in green synthesis, herein, we disclose a green route for the preparation of selenium/tellurium-substituted pyrimido­[1,2- b ]-indazoles from 3-aminoindazoles, ynals, and chalcogens via a visible light-induced three-component cascade reaction (Scheme b).…”
mentioning
confidence: 76%
“…In spite of these great advances in selenofunctionalization, visible light-induced three-component cascade cyclization with chalcogens has never yet been documented. Because of our continuing interest in green synthesis, herein, we disclose a green route for the preparation of selenium/tellurium-substituted pyrimido­[1,2- b ]-indazoles from 3-aminoindazoles, ynals, and chalcogens via a visible light-induced three-component cascade reaction (Scheme b).…”
mentioning
confidence: 76%
“…Now a days, C−H functionalization is a very simple and a momentous technique for the synthesis of wide range of organic compounds. Reactions like alkylation, arylation, [33] alkenylation, [34] vinylation, [35] sulphenylation, [36] phosphonylation, [37] cycloaddition, [38] sulphonylation, [22] N ‐sulphonyl alkenylation, [39] dithiocarbomation, [40] olefination, [35] propargylation [41] and allylation [42] could be successfully achieved by C−H functionalization of indolizines (Figure 2). The present review deals with the pioneering work in the field of C−H functionalization of indolizines since 2016.…”
Section: Scope Of the Reviewmentioning
confidence: 99%
“…Related work by the same group demonstrated that the use of rose bengal (RB) as a photocatalyst under visible-light irradiation could catalyze constructing pyrrolo[2,1,5- cd ]indolizine rings 16c in good to high yields ( Scheme 20 ). 27 Intermolecular [3 + 2] annulation of indolizines with internal alkynes under 20 W LED irradiation as an energy source using various photocatalysts such as RB, eosin Y, eosin B, rhodamine 6G, and fluorescein was carried out. The best results were obtained in the presence of RB.…”
Section: Synthesis Of N-heterocyclic Compoundsmentioning
confidence: 99%